A Blind Two-Stage Receiver for MIMO-CDMA Systems. (5th May 2011) - Hwang, Fuh-Hsin; Lin, Tsui-Tsai
Abstract : A blind two-stage multiple-input multiple-output (MIMO) receiver is proposed for code-division multiple access (CDMA) systems utilizing space-time block coding (STBC) over a multipath fading channel. Specifically, in the first stage, a signal-blocked (SB) interference-blocked (IB) detector is first constructed for collection of the desired signals and suppression of multiple access interference (MAI). In the second-stage, a decision-directed scheme is developed to alleviate desired signal cancellation. Computer simulations demonstrate that the proposed blind receiver can achieve a reliable output signal-to-interference-plus-noise ratio (SINR) performance approximating that of the optimal minimum mean squared error (MMSE) receiver and can exhibit the robustness against the finite data sample effect.